Affinity‐Triggered Assemblies Based on a Designed Peptide–Peptide Affinity Pair. Issue 11 (8th August 2019) - Fernandes, Cláudia S. M.; Pina, Ana S.; Moura Barbosa, Arménio J.; Padrão, Inês; Duarte, Filipa; Teixeira, Cátia A. S.; Alves, Vítor; Gomes, Paula; Fernandes, Tiago G.; Carvalho Dias, Ana M. G.; Roque, Ana C. A.
Abstract : Affinity‐triggered assemblies rely on affinity interactions as the driving force to assemble physically crosslinked networks. WW domains are small hydrophobic proteins binding to proline‐rich peptides that are typically produced in the insoluble form. Previous works attempted the biological production of the full WW domain in tandem to generate multivalent components for affinity‐triggered hydrogels. In this work, an alternative approach is followed by engineering a 13‐mer minimal version of the WW domain that retains the ability to bind to target proline‐rich peptides. Both ligand and target peptides are produced chemically and conjugated to multivalent polyethylene glycol, yielding two components. Upon mixing together, they form soft biocompatible affinity‐triggered assemblies, stable in stem cell culture media, and display mechanical properties in the same order of magnitude as for those hydrogels formed with the full WW protein in tandem. Abstract : WW domains bind to proline‐rich peptides. A small WW peptide is engineered as a minimal version of a full WW domain. The small ligand and the cognate target are conjugated to multivalent polyethylene glycol, generating two components that upon mixing yield a biocompatible hydrogel.